Design of Learning Video Using Realistic Mathematics Education Approaches to Developing the Problem-Solving Ability of Students of Class VII High School - Putra, Rinaldi Perdana; Suparman, S (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2018)
Problem solving is one of the important abilities in 21st century skills. Students who have low problem solving skills will have difficulty solving PISA and HOTS type problems. Learning media that have not integrated problem-solving skills will hinder the achievement of learning outcomes. This research has two objectives. First, this study aim to analyze the needs of learning media that are appropriate to students character, subject matter, and 2013 curriculum. Secondly, this research is to create a Realistic Mathematics Education approach learning video design to improve students’ problem solving abilities. This type of research is a research development with the 4D model. The subjects of this study were teachers and students of class VII. The research instruments used were interview guidelines, observation guidelines, questionnaires, and validation sheets. Interview guidelines are used to obtain information from teachers regarding the needs of learning media in the classroom. Data analysis uses the Miles Huberman model. This research resulted: the material taught in schools was in accordance with the 2013 curriculum, the learning video was not based on RME, the learning model applied by the teacher had not facilitated students to develop problem-solving skills, and the RME-based learning video design. This study concludes that RME-based learning videos that can improve students’ problem solving abilities need to be developed further.